x^2 = the first integer
(x - 1)^2 = the second integer.
x^2 - (x - 1)^2 = ?
First, let's plug a number into our equation for x.
(2)^2 - (2 - 1)^2 = ?
4 - (1)^2 = ?
4 - 1 = 3
As we can see the difference is odd but it's also the sum of the two consecutive integers.
2 + 1 = 3.
This works for all numbers. Let's plug another number into our equation for x.
(4)^2 - (4 - 1)^2 = ?
16 - (3)^2 = ?
16 - 9 = 7
4 + 3 = 7
Try any number and it will always be odd.
Answer:
Empirical probability
Step-by-step explanation:
Empirical probability is data collected from experiment and real-life situation.
The "empirical probability" of an outcome is obtained by dividing the frequency of occurrence of an event by the number of trails of the experiment.
![\Longrightarrow: \sf{P(E)=\dfrac{\text{number of times event occured}}{\text{number of trails}}](https://tex.z-dn.net/?f=%5CLongrightarrow%3A%20%5Csf%7BP%28E%29%3D%5Cdfrac%7B%5Ctext%7Bnumber%20of%20times%20event%20occured%7D%7D%7B%5Ctext%7Bnumber%20of%20trails%7D%7D)
- <u>Therefore, the correct answer is empirical probability.</u>
I hope this helps you! Let me know if my answer is wrong or not.
Answer:
5 + 2 x 9
Step 1 = 7 x 9
Step 2 = 63
Step-by-step explanation:
= 5 + 2 x 9
= 5 + ( 2 x 9 )
= 5 + 18
= 23
Step 2 = 7 x 9
= 63
Step 3 = 63
C. jin did not make a mistake
<em>Sorry </em><em>i'm </em><em>wrong </em><em>:</em><em>)</em>
Answer:
3
Step-by-step explanation: